In Vitro Comparison of Cefoxitin, Cefamandole, Cephalexin, and Cephalothin - Eickhoff, Theodore C. (1976)
The in vitro effect of cefoxitin, cefamandole, cephalexin, and cephalothin was tested against 645 strains of bacteria recently isolated from clinical sources. Against gram-positive organisms cephalothin and cefamandole were the most effective, generally being three- to fourfold more active than cephalexin or cefoxitin. Enterococci were not inhibited by less than 25 μg of any of the antibiotics per ml. Against Enterobacteriaceae, cefoxitin and cefamandole were the most active. An exception was the Enterobacter strains, against which cefoxitin was the least effective. None of the Pseudomonas aeruginosa strains were susceptible to 100 μg of any of the cephalosporins per ml. Cefamandole was the most active agent against Neisseria meningitidis and Neisseria gonorrhoeae. It was also the most effective agent against Haemophilus influenzae, even when taking into account a threefold inoculum effect.